Endoscopic Ultrasound-Guided Intratumoural Therapy for Pancreatic Cancer - Brian M Yan; Jacques Van Dam (Canadian Journal of Gastroenterology)
Pancreatic cancer is the second most frequent gastrointestinal malignancy and carries a dismal prognosis. The current standard of care includes resection, if possible, as well as systemic chemoradiation therapy. Endoscopic ultrasound (EUS) is an established technique for the diagnosis and staging of pancreatic adenocarcinoma. Interventional EUS via fine needle injection (FNI) for the treatment of pancreatic cancer is a rapidly expanding field. The present article reviews the up-to-date developments in EUS FNI for intratumoural pancreatic cancer therapy, including antitumoural agents, immunotherapy, ablative techniques and new delivery systems. The therapeutic modalities discussed are currently under development and will hopefully reach clinical practice if benefit is demonstrated through clinical trials. EUS FNI may be an exciting new technique for the delivery of desperately needed novel therapies for pancreatic cancer.